The regulatory role of N6-methyladenosine RNA modification in gastric cancer: Molecular mechanisms and potential therapeutic targets - Li, Gaofeng; Fu, Qiru; Liu, Cong; Peng, Yuxi; Gong, Jun; Li, Shilan; Huang, Yan; Zhang, Haiyuan (Frontiers in Oncology, 2022)
N6-methyladenosinen (m6A) methylation is a frequent RNA methylation modification. This RNA modification is regulated by three proteins, including “writers”, “erasers”, and “readers”. The m6A modification regulates mRNA stability, translation and degradation. Furthermore, m6A methylation influences non-coding RNA (ncRNA) processing, including cleavage, transportation, and degradation. Interestingly, recent research has linked m6A RNA modification to the occurrence and development of cancers, such as hepatocellular carcinoma, non-small cell lung cancer, and others. This review summarizes the regulatory role of m6A RNA modification in Gastric cancer (GC), including targets, mechanisms of action, and potential signaling pathways. This will aid in our understanding of the significance of m6A RNA modification in GC.